IDENTIFIKASI JENIS VEGETASI DOMINAN DI AREAL BEKAS KEBUN DAN KEBUN DI KAMPUNG AYAMBORI MANOKWARI (Identifying Dominant Vegetation In The Plantation Area And Former Farmland As The Indicator Of Soil Fertality At Ayambori Village – Manokwari) - Heru Joko Budirianto (Jurnal Natural, 2018)
The purpose of this study is to identify types of dominant vegetations in the plantation area and former farmland as indicator of soil fertility. Vegetation plays an important role to provide soil fertilities. Certain types, growing in the former farmland can possibly indicate soil fertilities both in the plantation area and former farmland. Aspect of the fertilities likely influences number of vegetative types and diversity of species. Measured vegetation is used to comparing species composition and its diversities. The former plantation that is taken up as sample has been used for 5 year. Identification of the type was carried out by using vegetative analysis. The valuable index was calculated to determine extensively the role of the dominant types from seeding and wooded phase. There are four different plot sizes. 20x20 meter is utilized purposively for wooded phase, 10x10 meter is pole, 5x5 is used as stake phase and 2x2 meter is made for seeding phase. The species which has important role for the soil fertilities are indentified through exploring various references and the result of interview from local society The finding reveals that vegetative composition in the former farmland which has been used for 5 year consists of three phases, including seeding, stake and pole. Totally, the types are 30 species under each phase. 23 types are in the seeding, 19 types contribute for pole and 6 types are resulted in the wooded phase. The dominant type of seedling phase is Lunasia amara, Piper aduncum is gotten in the stake phase, and the pole one is Mallotus philippensis. However, differently the plantation area carried out 39 species in the seeding phase, sapling phases has 36 species, pole phase carries out 16 species and 17 species is in the wooden phase. The dominant types is in the seeding and stake phase is Nephelium lappaceum, Lansium domesticum is pole phase, and Durio zibenthinus is resulted in the wooded phase